Hypothyroidism in Elderly Population: A Review - Akhtar Saifi; Alireza Ahmadi; Azadreza Mansourian (Golestan University Of Medical Sciences, 2017)
ABSTRACT Many metabolic disorders originate from thyroid disorders, particularly from hypothyroidism. Hypothyroidism commonly occurs in elderly subjects, particularly in women. Subclinical form of hypothyroidism can be diagnosed via laboratory testing. It is crucial to check thyroid hormone profile in elderly subjects. Subclinical hypothyroidism can eventually lead to overt hypothyroidism if left untreated. Treatment of subclinical hypothyroidism could be helpful in preventing the complications of hypothyroidism, particularly among the elderly population. The main aim of this review was to investigate subclinical hypothyroidism among elderly subjects. KEYWORDS: Hypothyroidism, Subclinical hypothyroidism, Elderly